PEMBERDAYAAN NELAYAN TALAGA RATU MELALUI DIVERSIFIKASI ALAT TANGKAP DAN DESIMINASI TEKNOLOGI BALE-BALE - Tuapetel, Friesland; Tupan, Charlotha I.; Lailossa, Grasiano Warakano (BAKIRA: Jurnal Pengabdian Kepada Masyarakat, 2025)
The village of Talaga Ratu in Kairatu Village, West Seram Regency, Maluku Province, is known as a fishing village that produces demersal fish and marlin. However, fishing activities around coral reefs can damage fish habitats, making it essential to protect the environment so that fish populations remain diverse and abundant. One way to achieve this goal is by introducing a variety of fishing gear. The bale-bale technology, a trap fishing gear, offers a solution for the utilization of fish resources, especially flying fish eggs, which have high economic value. This community service activity aims to transfer knowledge about flying fish egg fishing technology as an alternative livelihood for fishermen, to optimally and sustainably utilize the fisheries potential. This activity includes lectures and training on making bale-bale. The results of the questionnaires showed an increase in community understanding of fishing gear diversification. This creates new business opportunities with high market value, which in turn can improve the economy and preserve the coastal island ecosystem.